AFFIRMATIVE ACTION DAN POLITIK KEHADIRAN: KAJIAN FENOMENOLOGI SITI ROIKA SEBAGAI REPRESENTASI PEREMPUAN DI DPRD KOTA SEMARANG MELALUI PARTAI KEADILAN SEJAHTERA - Evan Kolef Manulang, Daniel; Indra Raya, Lanang; Riyadi, Sugeng; Krisna Wicaksana, Muhammad; Putri Junisya, Bania; Anggiana Rinjani, Audra; Zahrani Alaya, Yovita; Mufidah, Salsabila (Triwikrama: Jurnal Ilmu Sosial, 2024)
Having a quota of women in parliament is an important step to increase women's political participation and also reflects the commitment to gender equality, and becomes an opportunity for women to be able to provide their aspirations directly in public policy. Since the presence of female representatives in the Prosperous Justice Party (PKS), the party's internal atmosphere has changed. This is in accordance with Law No. 7 of 2017 concerning general elections, which stipulates that the list of legislative member candidates from Political Parties must contain at least 30% of the female quota. This applies to the provision of quotas for the DPR, Provincial DPRD, City DPRD and also in several other institutions. The existence of female representation, including currently many have contributed, one of which is by attending the "Women's Political Friends" meeting in Central Java. The affirmative action policy with the issue of female representation has brought many women to the political realm. This research was compiled using qualitative research methods with data collection techniques using interviews and literature studies.